Relapsing/refractory HL after autotransplantation: which treatment? - Di Renzo, Nicola; Gaudio, Francesco; Carlo Stella, Carmelo; Oppi, Sara; Pelosini, Matteo; Sorasio, Roberto; Stelitano, Caterina; Rigacci, Luigi (Acta Biomedica Atenei Parmensis, 2020)
For advanced-stage Hodgkin lymphoma (HL), front-line chemotherapy, alone or in combination with radiotherapy, leads to 5-year progression-free survival (PFS) rates and freedom-from-treatment failure (FFTF) rates of 70-85%, regardless of the chemotherapy regimen applied. Patients with HL experiencing disease progression during or within 3 months of front-line therapy (primary refractory) and patients whose disease relapses after a complete response have a second chance of treatment. The standard of care for relapsed or refractory HL is second-line chemotherapy followed by autologous stem cell transplantation (ASCT), which can induce long-term remission in approximately 40-50% of patients. However, HL recurrence occurs in about 50% of patients after ASCT, usually within the first year, and represents a significant therapeutic challenge. Allogeneic transplantation from HLA-matched donors represents the standard of care for patients with HL relapsing after- or refractory to ASCT.